Natural Tourism Park Development Strategy With The Concept Of Education, Recreation And Conservation Towards The Visiting Interest Of The Community Of Batam City - Fairuzzabadi, Fairuzzabadi; Sidabutar, Yuanita FD; Amelia, Cevy (UNIVERSITAS PAKUAN, 2024)
Sekupang Deer Park is located on Jalan RE. Martadinata, Tanjung Pinggir Village, Sekupang District is a new tourist icon in Batam City. This tourist park, which carries the